2018
DOI: 10.1093/nar/gky817
|View full text |Cite
|
Sign up to set email alerts
|

The RNA exosome contributes to gene expression regulation during stem cell differentiation

Abstract: Gene expression programs change during cellular transitions. It is well established that a network of transcription factors and chromatin modifiers regulate RNA levels during embryonic stem cell (ESC) differentiation, but the full impact of post-transcriptional processes remains elusive. While cytoplasmic RNA turnover mechanisms have been implicated in differentiation, the contribution of nuclear RNA decay has not been investigated. Here, we differentiate mouse ESCs, depleted for the ribonucleolytic RNA exosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 83 publications
1
48
0
Order By: Relevance
“…This RNA subset is enriched for short, intronless RNAs that are of similar length as TR. The mechanisms by which ZCCHC8 selectively targets this subset of RNAs to the nuclear RNA exosome remains unclear, but a similar signal for low abundance RNAs was also seen recently when RRP40, a noncatalytic nuclear RNA exosome component, was depleted in mouse embryonic stem cells (Lloret-Llinares et al 2018). RDH mRNAs have been shown to have a unique posttranscriptional processing pathway that did not involve adenylation (Marzluff et al 2008).…”
Section: Discussionmentioning
confidence: 59%
“…This RNA subset is enriched for short, intronless RNAs that are of similar length as TR. The mechanisms by which ZCCHC8 selectively targets this subset of RNAs to the nuclear RNA exosome remains unclear, but a similar signal for low abundance RNAs was also seen recently when RRP40, a noncatalytic nuclear RNA exosome component, was depleted in mouse embryonic stem cells (Lloret-Llinares et al 2018). RDH mRNAs have been shown to have a unique posttranscriptional processing pathway that did not involve adenylation (Marzluff et al 2008).…”
Section: Discussionmentioning
confidence: 59%
“…Furthermore, the previous transcriptional regulators were not recruited to the Gria1 according to publically available Hi-C data 33,65 ; TAD boundaries are denoted with dotted lines; H3K27me3 ChIP-seq signals in mESC are shown in green 9 ; CTCF binding sites in (green). The H3K27ac ChIP-seq data was obtained from 9 and the PRO-seq data to measured eRNA levels was obtained from 66 .…”
Section: Sox1(+35)tfbs+cgi and Sox1(+35)tfbs Inserts Became Strongly mentioning
confidence: 99%
“…Although our findings are in agreement with the original characterization of eRNAs, in which it was reported that eRNA synthesis requires the presence of a target promoter 49 , several recent studies have proposed that enhancers and promoters represent independent transcriptional units 67,68 . To assess whether our observations can be generalized, we compared eRNA production between three classes of active enhancers using nascent transcription and epigenomic data generated in ESC 66,69 : (I) enhancers located in TADs containing only poorly expressed genes; (II) enhancers located in a TAD with at least one gene with high expression levels; (III) enhancers whose closest gene within the same TAD has high expression levels (see Methods).…”
Section: Uncoupling Of H3k27ac and Erna Transcription During Enhancermentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, exosome was shown to be implicated in heat sock response in flies suggesting that function of the exosome in environmental adaptation is conserved(72). In addition to heat shock, exosome has been shown to play a role in cellular responses to nutrients, cell differentiation or DNA damage response in budding yeast and human(16,(73)(74)(75)(76).Although, these studies have revealed a prominent role of post-transcriptional regulation in mediating these responses, the underlying mechanisms responsible for selective regulation of the specific transcripts are currently not well understood. Our analysis has identified the RNA-binding protein Mub1 importance for the exosome dependent regulation of a subset of stress response genes in fission yeast, which helps to understand how these transcripts are regulated by the exosome and further highlights the important contribution of the nuclear RNA exosome in mediating adaption to environmental changes.…”
mentioning
confidence: 99%